Kesalehan atau Keterlibatan Digital? Komunikasi Kesalehan Influencer Berhijab di Instagram - Rofhani, Rofhani (UIN Sunan Ampel Surabaya, 2026)
This article examines how hijab-wearing influencers communicate piety through Instagram posts. Using a qualitative-descriptive approach, this study analyzes fifteen posts from three figures: Neelofa, Sashfir, and Sivia Azizah. The analysis focuses on three main elements: hijab or abaya visuals, captions, and features of digital circulation and personal branding. The findings indicate that digital piety is expressed not only through explicit religious messages but also through attire, poses, colors, self-narratives, religious occasions, hashtags, brand mentions, and image consistency. Neelofa displays piety through her hijab, intentions, family, knowledge, and simple fashion brands; Sashfir normalizes piety as a casual, urban, and aesthetic hijab lifestyle; while Sivia Azizah positions the abaya as a visual identity linked to worship, creativity, fashion, and the hashtag #MakeAbayaGreatAgain. This article asserts that piety and digital visibility cannot be strictly separated. Piety gains communicative power through platform logic, while visibility gains moral legitimacy through religious symbols and narratives. Thus, digital piety must be understood as a communicative practice shaped by visuality, personal narratives, the attention economy, and platform culture.